2022
DOI: 10.1002/brb3.2517
|View full text |Cite
|
Sign up to set email alerts
|

The quality of life in patients with Parkinson's disease: Focus on gender difference

Abstract: Background: To improve understanding of gender differences on quality of life (QoL) in patients with Parkinson's disease (PWP) of a different race, the differences of clinical features and health-related quality of life (HRQoL) between male and female PWP were studied in a small cohort early to middle stage of Chinese PWP. Methods:A cross-sectional study was carried out. PWP were consecutively included from April 2020 to July 2021 in Beijing Rehabilitation Hospital. HRQoL, motor symptoms, and nonmotor sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…A recent review reported a mean prevalence of hypersexuality of 3.5% in PD patients and quite convincing demographic data indicating that patients are often males on dopamine agonists [ 65 ]. Finally, females have significantly less social support, more psychological distress, and worse self-reported disability and health-related QoL compared to males [ 47 , 66 , 67 , 68 ]. In our analysis, we detected differences with a worse perception by females, especially in emotional well-being, pain, and discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review reported a mean prevalence of hypersexuality of 3.5% in PD patients and quite convincing demographic data indicating that patients are often males on dopamine agonists [ 65 ]. Finally, females have significantly less social support, more psychological distress, and worse self-reported disability and health-related QoL compared to males [ 47 , 66 , 67 , 68 ]. In our analysis, we detected differences with a worse perception by females, especially in emotional well-being, pain, and discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, NT1‐RBD patients were more often males compared with NT1‐noRBD (72.7% vs 33.3%). A male prevalence is well described in isolated RBD and is sometimes also found in PD‐RBD cohorts (Meng et al, 2022) while no gender difference has been described so far in narcoleptic patients with RBD (Antelmi et al, 2020). Whether a different percentage of males and females in these groups could affect our results is possible and this deserves further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the MoCA score correlated with a lower global efficiency of the white matter structural network in NT1 (Ni et al, 2022). However, it is important to consider that MoCA is a screening tool for detecting mild cognitive impairment (MCI) (Nasreddine et al, 2005), and some studies underline the importance of validating MCI cut-offs in independent samples, because they are likely to be sample dependent and specific to the individual investigation (Martin et al, 2017;Weissberger et al, 2017). These findings suggest caution in the interpretation of our results and encourage future studies to explore the cognitive functions in narcoleptic patients.…”
Section: Cognitive Profilementioning
confidence: 99%
“…The longer life expectancy of females may explain the higher proportion of elderly women over 85 years with PD. Although women have a lower risk of PD than men, they may get less medical support and have a higher risk of developing complications [24-26]. We did not have enough data to establish the detailed reasons for this discrepancy, but this could be the focus of future studies.…”
Section: Discussionmentioning
confidence: 99%